Analyzing the Relationship Between Urbanization and Greenhouse Gas Emissions: The Case of Kazakhstan - Bekturganova, M.S.; Kireyeva, A.A. (BUKETOV BUSINESS REVIEW, 2024)
Subject: The study analyses the relationship between urbanization and greenhouse gas (GHG) emissions in Ka zakhstan, looking at the impact of urban growth on GHG emissions and suggesting pathways for their sustainable de velopment. Methods: The study relies on national statistics and utilizes a hybrid method that integrates the analysis data anal ysis with qualitative insights. In this study, we used an algorithm that includes three key steps: (1) aggregating data from various sources for the period 2015–2021; (2) using data visualization tools to construct graphs; and (3) construct ing mind maps to visualize the consequences of urbanization for air quality. Findings: Our results show that urbanization in Kazakhstan is closely linked to a growth in GHG, driven by indus trial development, energy consumption, and transportation. The analysis highlights the importance of considering eco logical, economic, and social aspects of balanced development urban growth and reducing environmental impacts. Conclusions: The study also identifies opportunities to reduce emissions through strategic urban planning, green infrastructure development, and clean technology adoption. The study contributes to the current debate on sustainable urbanization by offering insights that can inform urban management policies and practices in Kazakhstan and similar contexts worldwide.